Analisis Aspek Hukum Kualitas Pelayanan BRT (Bus Rapid Transit) Trans Semarang - Sugiyanto Sugiyanto; Priskila Kurniawati (Public Service and Governance Journal, 2026)
One of the classic problems of Semarang City as a metropolitan city is related to the arrangement of the transportation system until now not resolved comprehensively. The arrangement of transportation in Semarang City as a trigger for the emergence of problems disproportionate number of vehicles to the number of passengers or residents compared to the volume of roads passed by motorized vehicles in Semarang City. With the increasing population of Semarang City on the one increasing motorized vehicles, the increasing number of motorized vehicles if not balanced with the number or volume of roads passed by motorized vehicles every day, every hour has the consequence of congestion and chaos on several roads in Semarang City. Referring to these conditions, the Semarang City Government is trying to overcome transportation problems by organizing road-based public transportation known as BRT or Bus Rapid Transit Trans Semarang which was first rolled out on September 18, 2009. The legal aspects that underlie the BRT (Bus Rapid Transit) Trans Semarang service are Law No. 22 of 2009, No. 25 of 2009. The Trans Semarang Bus Rapid Transit (BRT) service is expected to address transportation management issues in Semarang, a growing metropolitan city. In this qualitative study, the researcher describes the quality of BRT implementation in Semarang from a legal perspective.